PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF DEVELOPING CREATIVE ACTIVITY IN FUTURE EDUCATORS BASED ON A FUNCTIONAL APPROACH - Nurjanova, Raykhon Urazbaevna (SCIENCE and SOCIETY, 2026)
This article describes the pedagogical and psychological features of the development of creative activity in future educators based on a functional approach, creative activity, new approaches in the professional activity of a teacher, the progressive direction of professional pedagogical activity, the relationship between thinking and creativity.